Effect of pulsed electric fields and high pressure on improved recovery of high‐added‐value compounds from olive pomace. Issue 5 (8th April 2020) - Andreou, Varvara; Psarianos, Marios; Dimopoulos, George; Tsimogiannis, Dimitrios; Taoukis, Petros
Abstract: Olive pomace is considered a solid by‐product and a rich source of valuable compounds such as polyphenols, flavonoids with antioxidant properties, and proteins. Nonthermal technologies, which cause alterations to cell permeability, are being explored to assist conventional recovery techniques. The aim of this study was to assess the effect of pulsed electric fields (PEF) and high pressure (HP) on improved recovery yield of the high‐added‐value compounds or to shorten the extraction time of these compounds. Olive pomace ( Tsounati cv ) was pretreated with PEF (1.0 to 6.5 kV/cm, 0.9 to 51.1 kJ/kg, and 15 µs pulse width) or HP (200 to 600 MPa and 0 to 40 min). Evaluation of the intracellular compounds extracted via solid–liquid extraction (50% ethanol–water solution) was performed. More intense PEF and HP conditions resulted in a significant increase of the phenolic concentration up to 91.6% and 71.8%, respectively. The increased antioxidant capacity of each extract was correlated to phenolic compound concentration. The protein concentration that was achieved with PEF pretreatment was doubled; however, HP‐pretreated extracts reached 88.1% higher yield than untreated for pressures up to 200 MPa. HP and PEF pretreatment decreased extraction completion time t 98 (needed time to recover the equal amount of phenolics and proteins of untreated after 60 min of conventional extraction) to 12 min and lower than 1 min, respectively. To conclude, both pretreatments are effective in improving the conventional extraction process for increased yield recovery of high‐added‐value compounds from olive pomace.